High-resolution Spectroscopic Analysis of Four Unevolved Barium Stars - M. P. Roriz; N. Holanda; L. V. da Conceição; S. Junqueira; N. A. Drake; A. Sonally; C. B. Pereira (The Astronomical Journal, 2024)
A classical local thermodynamic equilibrium analysis, based on high-resolution spectroscopic data, is performed for a sample of three potential barium dwarf candidates and one star already recognized as such. We derived their atmospheric parameters, estimated their masses and luminosities, and determined chemical abundances for a set of 21 elements, including CNO. Some elemental abundances are derived for the first time in HD 15096, HD 37792, and HD 141804. The program stars are dwarfs/subgiants with metallicities typical of disk stars, exhibiting moderate carbon enhancements, with [C/Fe] ratios ranging from +0.29 to +0.66 dex, and high levels of slow neutron-capture ( s -process) elements, with [ s /Fe] ≳ + 1.0 dex. As spectroscopic binaries, their peculiarities are attributable to mass transfer events. The observed neutron-capture patterns of were individually compared with two sets of s -process nucleosynthesis models (Monash and fruity ), yielding dilution factors and masses estimates for the former polluting asymptotic giant branch stars. Low-mass (≲3.0 M _⊙ ) models successfully reproduce the observations. In addition, we estimated mean neutron exposures on the order of 0.6–0.7 mb ^−1 for the s -processed material observed in their envelopes. Applying an empirical initial-final mass relation, we constraint in ∼0.7 M _⊙ the mass of their dim white dwarf companions. Moreover, our kinematic study revealed that the program stars are members of the thin disk, with probabilities greater than 70%. Hence, we identified HD 15096 and HD 37792 as new barium dwarfs and confirmed that HD 141804 is a barium dwarf. Thus, the number of barium dwarfs identified in the literature from high-resolution spectroscopy increases to 71 objects.